The Impact of Legal Pluralism on Human Rights Protection in Health Services - Fenti Maya Sari; Syifa Nur Lathifah; I Putu Wahyu Budhi Sucita; Dedi Putra (Rechtsvinding, 2026)
This research aims to analyze the influence of legal pluralism on the realization of human rights protection within the national health service system and to identify the juridical and sociological obstacles arising from normative conflicts between state law and local customary norms. A normative juridical approach is employed, focusing on the analysis of various regulations, norms, and legal doctrines pertaining to human rights protection in the healthcare system, supported by library research techniques involving primary, secondary, and tertiary legal materials analyzed qualitatively through legal interpretation. Interaction between state law and local norms frequently exhibits a dominative-subordinative pattern that triggers tension, where rigid formal health regulations often clash with beliefs or traditional customs held by local communities. Individuals are often placed in vulnerable positions when forced to choose between formal medical procedures and obedience to customary authority, resulting in various human rights violations such as access discrimination, disregard for informed consent, and the denial of life-saving medical actions that contradict human rights principles. Neglect of this legal pluralism creates a dangerous zone for fundamental human rights, necessitating concrete steps such as policy synchronization, formalization of safe traditional medical practices, strengthening legal literacy, and cross-element dialogue to harmonize state law and local norms, thereby ensuring consistent and equitable rights to health.